2010
DOI: 10.1160/th09-04-0223
|View full text |Cite
|
Sign up to set email alerts
|

Severe malaria is associated with a deficiency of von Willebrand factor cleaving protease, ADAMTS13

Abstract: Severe falciparum malaria remains a major killer in tropical countries. Central in the pathophysiology is mechanical obstruction in the microcirculation caused by cytoadherence and sequestration of parasitized erythrocytes. However, the pathogenesis of many features complicating severe malaria, including coma, renal failure and thrombocytopenia, remains incompletely understood. These disease manifestations are also key features of thrombotic thrombocytopenic purpura, a life-threatening disease strongly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…This process may ultimately result in organ dysfunction as described previously in several other pathologies and invasive procedures including TTP and liver transplantation (4,5,(20)(21)(22)(23)(24). We speculate that the development of a VWF/ADAMTS13 unbalance during lung transplantation also facilitates thrombus formation within the allograft.…”
Section: Primary Hemostasis In Lung Transplantationsupporting
confidence: 59%
“…This process may ultimately result in organ dysfunction as described previously in several other pathologies and invasive procedures including TTP and liver transplantation (4,5,(20)(21)(22)(23)(24). We speculate that the development of a VWF/ADAMTS13 unbalance during lung transplantation also facilitates thrombus formation within the allograft.…”
Section: Primary Hemostasis In Lung Transplantationsupporting
confidence: 59%
“…48 Previous studies have reported modest reductions in plasma ADAMTS13 activity levels in children with P falciparum infection. 17,21,22 In contrast, we observed no significant change in murine plasma ADAMTS13 activity following P berghei infection ( Figure 3B). In addition, despite the presence of circulating UL-VWF, peripheral blood film examination demonstrated no significant features of microangiopathic hemolytic anemia ( Figure 3C).…”
mentioning
confidence: 71%
“…In contrast, previous studies did report a mild reduction in plasma ADAMTS13 activity (using both FRETS-VWF75 and fulllength VWF cleavage assays) in children and adult patients with severe malaria compared with healthy controls. 17,21,22 Importantly, however, residual plasma ADAMTS13 levels in African children with CM still remained higher than 60%, which should be sufficient to prevent the accumulation of hyperreactive UL-VWF multimers. …”
mentioning
confidence: 99%
“…Indeed, after an analysis of the literature on changes in VWF/ADAMTS13 in these pathologies, we found that a proportion of the studies had either no or only partial evidence of ultralarge VWF appearance in the systemic circulation. [3][4][5] Activation of the fibrinolytic system may thus prevent the formation of platelet thrombi in these disorders. Consequently, thrombolytic therapy may slow down the progression to multiorgan failure by preventing or reducing thrombus formation within solid organs.…”
Section: To the Editormentioning
confidence: 99%